Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate) scaffolds – a step towards ligament repair applications - Thammarit Khamplod; James B. Winterburn; Sarah H. Cartmell (Science and Technology of Advanced Materials)
The incidence of anterior cruciate ligament (ACL) ruptures is approximately 50 per 100,000 people. ACL rupture repair methods that offer better biomechanics have the potential to reduce long term osteoarthritis. To improve ACL regeneration biomechanically similar, biocompatible and biodegradable tissue scaffolds are required. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), with high 3-hydroxyvalerate (3HV) content, based scaffold materials have been developed, with the advantages of traditional tissue engineering scaffolds combined with attractive mechanical properties, e.g., elasticity and biodegradability. PHBV with 3HV fractions of 0 to 100 mol% were produced in a controlled manner allowing specific compositions to be targeted, giving control over material properties. In conjunction electrospinning conditions were altered, to manipulate the degree of fibre alignment, with increasing collector rotating speed used to obtain random and aligned PHBV fibres. The PHBV based materials produced were characterised, with mechanical properties, thermal properties and surface morphology being studied. An electrospun PHBV fibre mat with 50 mol% 3HV content shows a significant increase in elasticity compared to those with lower 3HV content and could be fabricated into aligned fibres. Biocompatibility testing with L929 fibroblasts demonstrates good cell viability, with the aligned fibre network promoting fibroblast alignment in the axial fibre direction, desirable for ACL repair applications. Dynamic load testing shows that the 50 mol% 3HV PHBV material produced can withstand cyclic loading with reasonable resilience. Electrospun PHBV can be produced with low batch variability and tailored, application specific properties, giving these biomaterials promise in tissue scaffold applications where aligned fibre networks are desired, such as ACL regeneration.